From digitalization to green transformation: empirical evidence from RCEP’s industrial sectors - Lu Wan; Xiya Wan; Yanqi Fang; Guohua Huang (Humanities & Social Sciences Communications, 2025)
Abstract Within the context of global industrial chain reconfiguration, the Regional Comprehensive Economic Partnership (RCEP) presents an array of collaborative opportunities for nations to foster industrial transformation. This study provides novel insights into the environmental implications of regional trade accords, focusing on the nexus between cross-border industrial integration, a hallmark of RCEP, and the advancement of green technologies within China’s manufacturing sectors. Utilizing panel data from 11 RCEP member countries spanning 2011–2019, we employ the fixed effect, mediating effect, and moderating effect models to evaluate the impact of service industry digitalization. Our findings indicate that while the digitalization of services under the RCEP significantly propels the green technology development in China’s manufacturing, this beneficial effect is dampened by increasingly rigid regulations governing digital services trade. The operational proficiency and innovative capacity of the manufacturing sector emerge as pivotal mediators in this dynamic. Conversely, the digitalization of service industries impedes the green transformation of technology-intensive manufacturing industries. Collectively, these insights elucidate the environmental repercussions of industrial digitization and affirm the environmental benefits of collaborative regional industrial chains.